Design and development of telemedicine based heartbeat and body temperature monitoring tools. Issue 1 (May 2020) - Gunawan, I P C; Andayani, D H; Triwiyanto, T; Yulianto, E; Rahmawati, T; Soetjiatie, L; Musvika, S D
Abstract: Body temperature and heart rate monitoring based on telemedicine is an electromedical device served to determine the condition of the heart rate per minute (BPM) and the patient's body temperature in realtime remotely. The purpose of this study is to design the heart rate and body temperature monitor based on telemedicine uses the Internet of Things (IoT). The system allows unlimited distance monitoring by utilizing the internet as a medium for sending the data. The body temperature and heart rate monitoring system uses DS18B20, Arduino, and Raspberry Pi temperature sensors and finger sensors as data processing and transmission microprocessors, LCD Character displays the results of heart rate readings and body temperature per minute. The results of heart rate measurements and body temperature are sent to the database via microservice and displayed on a web page in the form of numerical data and responsive plot graphics on desktops and mobile phones. Based on the measurement and comparison to standard apparatus, the average error of BPM measurement is 0.72%, with a maximum permissible tolerance of ± 5%. While in the body temperature parameter the average difference is 0.3 ° C with a maximum permitted tolerance of ± 1 °C.